SIM.QM-S10: supplementary comparison for trace elements in skim milk powder - Grinberg, Patricia; Mester, Zoltan; Gatti, Patricia; Acosta, Osvaldo; Puelles, Mabel; Delgado, Mabel; Sena, Rodrigo Caciano de; Almeida, Marcelo Dominguez de; Rocha, Marcia Silva da; Sandoval, Soraya; Núñez, Claudia; Vera, Javier; et al. (IOP Publishing, 2021)
Main text SIM.QM-S10 was performed to assess the analytical capabilities of National Metrology Institutes (NMIs) and Designated Institutes (DIs) of SIM members (or other regions) for the accurate determination of trace metals in skim milk powder. The study was proposed by the coordinating laboratories National Research Council Canada (NRC) and INTI Argentina as an activity of Sistema Interamericano de Metrología (SIM) approved by the Inorganic Analysis Working Group (IAWG) of Consultative Committee for Amount of Substance - Metrology in Chemistry and Biology (CCQM). Participants included NMIs/DIs from twelve countries. No measurement method was prescribed by the coordinating laboratories. Therefore, NMIs used measurement methods of their choice. However, the majority of NMIs/DIs used closed vessel microwave system using a mixture of HNO 3 and H 2 O 2 for the digestion and ICP-MS and ICP-OES for the determination of the measurands. One laboratory used INAA technique. This SIM.QM-S10 Supplementary Comparison provides NMIs/DIs with the needed evidence for CMC claims for trace elements in skim milk powder and similar matrices. To reach the main text of this paper, click on Final Report . Note that this text is that which appears in Appendix B of the BIPM key comparison database kcdb.bipm.org/ . The final report has been peer-reviewed and approved for publication by the CCQM, according to the provisions of the CIPM Mutual Recognition Arrangement (CIPM MRA).